Anthropometric measurements of a neonate vis-a-vis maternal nutritional status - Singh, Surinder; Kumar, Pancham; Thakur, B. R. (International Journal of Contemporary Pediatrics, 2018)
Background: The incidence of low birth weight i.e. <2500gm babies in India is 30-40% as compared to 7.5% in the developed world. The objective of this study was to find correlation between neonatal anthropometric indices and maternal nutritional status. Methods:Out of one thousand twelve live births during the study period 529 newborns which were fulfilling the required criteria were enrolled in the study. All the enrolled newborns were assessed for weight, length, OFC, MAC, MAC/OFC and Ponderal index. Maternal nutritional status was assessed by maternal weight, maternal height and BMI. Maternal data also comprised of demographic and social factors viz. maternal age, socioeconomic status, dietary habits, maternal education, occupation, parity, residence, altitude and antenatal care. The correlation between neonatal anthropometric indices and maternal nutritional status was studied using appropriate statistical methods. Results: The study population had mean maternal weight 50.0593±7.97, mean maternal height 154.148±9.0388 and mean body mass index 21.5871±10.458 which were significantly higher than national figure (NFHS 2 data). The mean birth weight was 2822.80±447.64, mean length 48.0319±2.1963, mean OFC 33.6866±1.3510, mean MAC 8.8866±0.8349,MAC/OFC 0.2636±2.039 E-02 .The study showed 29% LBW babies. The study showed highly significant positive relationship between maternal nutritional status assessed by maternal weight, height and BMI; and neonatal anthropometry i.e. birth weight length, OFC MAC, and MAC/OFC ratio. Conclusions:Maternal nutritional status has strong linear correlation with neonatal anthropometry. Shorter and lighter mothers tend to give birth to small babies with lower anthropometric measurements. Improvement in the maternal nutritional status can lead to better neonatal anthropometric indices which can be helpful in decreasing the neonatal morbidity and mortality.